Local Government Strategies to Reduce Unemployment - M. Harry Mulya Zein; Harta Danay; Sisca Septiani (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2023)
Purpose – This study aims to know and analyse the strategy of the Padang City government through the Manpower and Industry Office in reducing unemployment, to know and analyse the supporting and inhibiting factors of local governance strategy in reducing unemployment, to know and analyse efforts to overcome the inhibiting factors of local government strategy in reducing unemployment in Padang City Province West Sumatra.Methodology – The method used in this study is qualitative, using a descriptive approach. This study analyses and explains the governance strategy of Padang City in reducing unemployment. Data collection techniques were used using interviews, questionnaires, and documentation. The research instrument consists of interview guidelines, SWOT questionnaires, and documents. The analysis technique used is SWOT analysis.Findings – The Padang City Government has made reducing unemployment a key target by reconstructing the organizational structure of the Manpower and Industry Office to improve effectiveness and efficiency. There was an increase in budgets and training facilities for developing labour quality, which received an enthusiastic response from the workforce. However, several challenges still exist, such as inadequate cooperation with the private sector, management information systems that are not optimal, the availability of inadequate facilities and infrastructure, and difficulties in reaching large areas in Padang City.Originality/Novelty – This research focuses on the strategies implemented by local governments and the inhibiting factors in their implementation. It provides an in-depth understanding of the challenges and how to overcome them.Implications – Developing efficient management information systems, investment in technology, and local collaboration is critical in tracking labour force data and assessing programs—adequate facilities and infrastructure, larger budget allocations, and support skills training. Strategic partnerships with industry and increased information and support to job seekers ensure the suitability of training to market needs. In line with this, coordinated national policies and long-term strategies provide a consistent framework for local interventions.